Do Asian Values Still Exist? Revisiting the Roots in Search of a Plausible Future. (March 2014) - Sen, Parama
In a world ripped with conflicting issues stemming from varying interests and pressing common concerns, the role of culture and tradition seems to have gained greater salience. At the core of Asia's cultural assertiveness lies the concept on Asian values. Claimed to be rooted in Confucianism, the discourse appeals to the communitarian Asian tradition pitting it against the individualism of the West. While the use of the concept to explain the economic prosperity of East and Southeast Asia and as a counterforce to globalisation was thwarted by the Asian financial crisis, the belief that Asia and Asians subscribed to a value system fundamentally different from that of the West lingered on. This article seeks to analyse the contemporary relevance of the concept of Asian values and delve into its roots in an attempt to attune it to current realities.